DAP’s opposition of Malaysia as an Islamic State - P. Rajanthiran, R. Sivaperegasam (Institute of Tun Dr. Mahathir Mohamad’s Thoughts, Universiti Utara Malaysia, 2010)
The brave and controversial declaration of Malaysia as an Islamic state by YABhg Tun Dr. Mahathir Mohamad on the 29 September 2001, was vehemently opposed by the DAP. This paper analyses and explores the justification of the said declaration as well as the pattern and rationale for DAP’s oppositionism. The DAP had specifically highlighted and protested via its “929” campaign that YABhg Tun Dr. Mahathir Mohamad’s declaration of Malaysia as an Islamic state was unconstitutional, undemocratic and arbitrary. The DAP party stalwarts maintained that Malaysia was a secular state since Independence and ought to continue remaining so in the best interests of a pluralistic Malaysia. The primary focus of this paper therefore is to identify and discuss the flaws in the DAP’s said claim, and instead highlight the fact that Malaysia is rightfully an Islamic state from Independence and beyond. YABhg Tun Dr. Mahathir’s declaration of Malaysia as an Islamic state is the climax of the Islamisation policy conducted throughout to put Malaysia back on the world map as a reputable Islamic state just as how it had been during the days of the precolonisation era.